2020
DOI: 10.1016/j.jctube.2020.100205
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of the mean corpuscular volume and CD4/CD8 ratio in discriminating between rifampicin resistant and rifampicin sensitive tuberculosis

Abstract: Background There is need for simple, cost effective and widely available point of care tests for low level health facilities in developing countries to screen for drug resistant tuberculosis (TB) after bacteriological confirmation of TB by smear microscopy. We evaluated the sensitivity and specificity of the mean corpuscular volume (MCV) and CD4/CD8 ratio in discriminating between rifampicin resistant (RR-TB) and rifampicin sensitive (RS-TB) tuberculosis. Methods We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have suggested that MCV is a marker of pulmonary inflammation (Abba, 2009) and that MCV levels are negatively correlated with bacillary load in the lungs (Baruch Baluku et al, 2020). ESR is an inflammatory index, which can reflect the state of TB.…”
Section: Diagnostic Performance Of the Scoring System In The Training...mentioning
confidence: 99%
“…Previous studies have suggested that MCV is a marker of pulmonary inflammation (Abba, 2009) and that MCV levels are negatively correlated with bacillary load in the lungs (Baruch Baluku et al, 2020). ESR is an inflammatory index, which can reflect the state of TB.…”
Section: Diagnostic Performance Of the Scoring System In The Training...mentioning
confidence: 99%